2011 IEEE International Ultrasonics Symposium 2011
DOI: 10.1109/ultsym.2011.0428
|View full text |Cite
|
Sign up to set email alerts
|

Growth of AlN oriented films on insulating substrates

Abstract: Abstract-This work describes the structural and piezoelectric assessment of aluminum nitride (AIN) thin films deposited by pulsed-DC reactive sputtering on insulating substrates. We investígate the effect of different insulating seed layers on AIN properties (crystallinity, residual stress and piezoelectric activity). The seed layers investigated, silicon nitride (SÍ3N4), silicon dioxide (Si0 2 ), amorphous tantalum oxide (Ta 2 O s ), and amorphous or nano-crystalline titanium oxide (Ti0 2 ) are deposited on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These revealed that despite being grown on the TiO x seed layers, all the films exhibited a significant piezoelectric activity with values of the electromechanical coupling factor ^SAW ranging between 0.6% and 1.2%, which have been associated to coupling factors ^BAW in BAW resonators operating in the longitudinal thickness mode ranging from 3% to 5% [17,19]. On the one hand, the experimental data of Figs.…”
Section: Results and Dicussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These revealed that despite being grown on the TiO x seed layers, all the films exhibited a significant piezoelectric activity with values of the electromechanical coupling factor ^SAW ranging between 0.6% and 1.2%, which have been associated to coupling factors ^BAW in BAW resonators operating in the longitudinal thickness mode ranging from 3% to 5% [17,19]. On the one hand, the experimental data of Figs.…”
Section: Results and Dicussionmentioning
confidence: 96%
“…Finally, substrates of type III were composed exclusively of insulating materials; as substrates we used Corning glass plates 500 urn-thick which were covered with five insulating layers of Si0 2 The piezoelectric AIN film was deposited directly on top of the mirror without bottom electrode. Titanium oxide (TiO x ) seed layers were used to promote the growth of highly c-axis oriented films [17]. Finally, a molybdenum (Mo) layer was grown on top of the AIN film and patterned into coplanar electrodes of different geometries shown in figure 2.…”
Section: Methodsmentioning
confidence: 99%